2018
DOI: 10.1158/1078-0432.ccr-17-1114
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib/II Trial of NC-6004 (Nanoparticle Cisplatin) Plus Gemcitabine in Patients with Advanced Solid Tumors

Abstract: Purpose: NC-6004, a novel cisplatin nanoparticle developed using micellar technology exhibits sustained release of cisplatin and selective distribution to tumors. Preclinical data demonstrated a favorable tolerability profile and preserved or improved antitumor activity compared with cisplatin across animal models. We evaluated the safety and tolerability of NC-6004 and gemcitabine using a Bayesian continual reassessment model (N-CRM) to determine the optimal dose.Experimental Design: Patients with advanced so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Besides the cited pharmacological properties, the nanoformulation also improved the physicochemical properties of drugs and could be engineered in order to modify their surface for active targeting [258][259][260]. Several nanoparticle formulations, such as lipids and polymer-based materials, have already been approved and are in use [20,261,262]. Although such nanocarriers show good pharmacokinetic and safety profiles, together with enhanced bioavailability, the use of naturally occurring EEVs could be of help in overcoming the off-target effects of lipidand polymer-based nanocarriers since EEVs are naturally covered with several biomolecules useful for tumor targeting [263,264].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the cited pharmacological properties, the nanoformulation also improved the physicochemical properties of drugs and could be engineered in order to modify their surface for active targeting [258][259][260]. Several nanoparticle formulations, such as lipids and polymer-based materials, have already been approved and are in use [20,261,262]. Although such nanocarriers show good pharmacokinetic and safety profiles, together with enhanced bioavailability, the use of naturally occurring EEVs could be of help in overcoming the off-target effects of lipidand polymer-based nanocarriers since EEVs are naturally covered with several biomolecules useful for tumor targeting [263,264].…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, some areas need further investigation in order to overcome currently poor translational outcomes of nanomedicine, such as identifying the mechanisms of nanoparticles' interaction with different tissues and their uptake in the body [191]. [194] Squamous Cell Carcinoma of the Head and Neck…”
Section: Clinical Landscape and Challengesmentioning
confidence: 99%
“…The MTD of NC-6004 was 135 mg/m 2 , which is 50% higher than the MTD determined using a traditional 3+3 modified Fibonacci dose escalation design in a previous trial of NC-6004 that reported no clinically significant neuro, oto, or nephrotoxicity. In the Phase II portion of this study, which is reported here, an adaptive, open-label expansion trial was conducted at the MTD dose identified in the first phase in patients with squamous NSCLC, biliary tract, or bladder cancer; treatment efficacy, safety, and tolerability were assessed [9].…”
Section: Research Papermentioning
confidence: 99%